Editors' note - John Kingston; Claire Moore-Cantwell; Joe Pater; Robert Staubs (Amherst demo, 2014)
This is a brief note about the origin of the papers as presentations at Phonology 2013 held at the University of Massachusetts Amherst, and acknowledgments for help with the conference and proceedings.